Managing Diversity in the Multicultural Framework of India - Adil Bashir Parry (East Asian Journal of Multidisciplinary Research, 2022)
After India got independence from the British rule in 1947, the main challenge for the makers of the new constitution was the successful management of the vast ethno-cultural, religious and linguistic diversity of the country. Accommodating minorities in a way that respects their distinctive identity was indeed a great task for constitutional makers. The paper, therefore, intends to study the role of Indian constitution in protecting the deep-rooted diversity of India. It seeks a detailed analysis of the general and specific provisions of the constitution that guarantees the minorities not only a safe survival but their empowerment as well. The study found Indian constitution a multicultural document that ensures minorities a dignified status by conferring them some special rights available only to them.